(untitled) (Journal of Bio-Science, 2011)
Context: In the last few decades an ample array of molecular techniques has been introduced to obtain new disposition for the classification of Trichoderma species. Today the concern of scientists is either in the direction of gene targeting or ribotyping, the newest fingerprinting tool for genomic DNA that contain all or part of the genes coding for 18S rRNA in eukaryotes. Objectives: To take advantage of advanced molecular techniques for phylogenetic analysis of indigenous isolates of Trichoderma to comprehend our knowledge of this genus by supplementing the phenotypic identification. Materials and Methods: Genomic DNA of twenty four isolates of Trichoderma species (T. harzianum, T. hamatum, T. koningii and T. pseudokoningii) were extracted by CTAB method and indicated band of 15Kb on 0.8% agarose gel. Quality of DNA was determined by obtaining absorbance ratio (260/280) in the range of 1.7-1.9. Restriction fragment length polymorphism (RFLP) analyses were performed by using two restriction endonulease enzymes i.e., BamHI and HindIII. The BamHI represented results in the range of 500bp-750bp. 18S rRNA gene targeting was further carried out through optimization in ribotyping analysis. Results: The DNA bands of 24 isolates of Trichoderma species were compared with marker DNA bands and indicated the presence of genomic DNA intact band of 15Kb. The ratio of absorbance 260/280nm (1.8-1.9 for pure DNA preparations) provided an estimate of the purity of the DNA RFLP analysis, along with the negative control of twenty four different isolates of Trichoderma species subjected to restriction using BamHI enzyme. The rRNA gene amplified band was observed at 600bp in the case of T. hamatum isolate (S. cumini stem bark, FCBP accession number 769) while in remaining isolates bands were in slightly smeared form. Furthermore, rRNA gene amplification conditions were optimized by altering different Tm and MgCl2 concentrations. Conclusion: The genomic DNA can serve as long term storage of information. Therefore advance molecular techniques can be used to study the variability in the genome of organism. RFLP are the initial steps for screening the genome of any organism. Key words: Trichoderma; DNA; RFLP; restriction endonuleases; 18S rRNA. DOI: 10.3329/jbs.v17i0.7117 J. bio-sci. 17: 117-122, 2009